(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The study sought to highlight the importance of applying the administrative control procedures which play an important role in assessing the performance of the employees of the tax administration and specifically the companies department by setting the standards and objectives of the department on the basis of which in the implementation of its work and identify deviations and errors and find appropriate solutions and evaluate the results according to appropriate solutions, The study of the problem of research, namely the extent to which the tax administration applied to the administrative control procedures in view of its importance in evaluating the performance of its employees and the extent of their application to the legislations and laws related to the taxpayers and raising their performance Its tax as planned, and was based on research on the main premise that ((the application of administrative control procedures working to improve the efficiency of tax administration employees and achieve tax proceeds as planned.